The effect of consonant type on fundamental frequency and larynx height in Danish - Reinholt Petersen, Niels (ARIPUC, 1983)
Fundamental frequency (Fo) and larynx height were measured in words of the type 'CV:fi where the initial consonant varied in both manner and place of articulation. The main findings were a clear effect of voicing in the obstruents [f] and [v] on both Fo and larynx height in the following vowel, a small but consistent effect of aspiration on Fo but not on larynx height in the following vowel, and an effect of place of articulation on larynx height which was not, however, reflected in Fo.